How to wash a woolly mammoth - Robinson, Michelle (Michelle Jane), 1977- (Henry Holt and Company, 2014)
"Follow this step-by-step guide to successfully clean up your hairy friend. But be forewarned. A mammoth's tummy is terribly tickly"--